Disengagement is as revealing as prosocial action for young children's responding to strangers in distress: How personal distress and empathic concern come into play. (November 2020) - Lin, Hung-Chu; Janice, Josephine
In a paradigm of simulated stranger distress designed to elicit empathic arousal, this study examined multiple elements of responding in 61 preschoolers. Disengagement from stranger distress was underscored in addition to prosocial responding. All children encountered a female adult stranger feigning stomach ache followed by an infant manikin emitting cry sound in a bassinet. Behaviors were coded for other-oriented behaviors, personal distress, and disengagement. In contrast to the traditional supposition, behaviors indicative of personal distress covaried positively with empathic concern and negatively with disengagement. The findings of multiple regression analysis demonstrated how empathic concern and personal distress jointly related to disengaging behaviors in children's response to stranger distress.